Resistance Training with Co-ingestion of Anti-inflammatory Drugs Attenuates Mitochondrial Function - Cardinale, Daniele A.; Lilja, Mats; Mandić, Mirko; Gustafsson, Thomas; Larsen, Filip J.; Lundberg, Tommy R. (Frontiers in Physiology, 2017)
Aim: The current study aimed to examine the effects of resistance exercise with concomitant consumption of high versus low daily doses of non-steroidal anti-inflammatory drugs (NSAIDs) on mitochondrial oxidative phosphorylation in skeletal muscle. As a secondary aim, we compared the effects of eccentric-overload with conventional training. Methods: Twenty participants were randomized to either a group taking high doses (3 x 400 mg/day) of ibuprofen (IBU; 27±5 yr; n=11) or a group ingesting a low dose (1 x 75 mg/day) of acetylsalicylic acid (ASA; 26±4 yr; n=9) during 8 weeks of supervised knee extensor resistance training. Each of the subject’s legs were randomized to complete the training program using either a flywheel (FW) device emphasizing eccentric-overload, or a traditional weight stack machine (WS). Maximal mitochondrial oxidative phosphorylation (CI+IIP) from permeabilized skeletal muscle bundles was assessed using high-resolution respirometry. Citrate synthase (CS) activity was assessed using spectrophotometric techniques and mitochondrial protein content using western blotting. Results: After training, CI+IIP decreased (P<0.05) in both IBU (23%) and ASA (29%) with no difference across medical treatments. Although CI+IIP decreased in both legs, the decrease was greater (interaction p = 0.015) in WS (33%, p = 0.001) compared with FW (19%, p = 0.078). CS activity increased (p = 0.027) with resistance training, with no interactions with medical treatment or training modality. Protein expression of ULK1 increased with training in both groups (p < 0.001). The increase in quadriceps muscle volume was not correlated with changes in CI+IIP (R=0.16). Conclusion: These results suggest that 8 weeks of resistance training with co-ingestion of anti-inflammatory drugs reduces mitochondrial function but increases mitochondrial content. The observed changes were not affected by higher doses of NSAIDs consumption, suggesting that the resistance training intervention was the prime mediator of the decreased mitochondrial phosphorylation. Finally, we noted that flywheel resistance training, emphasizing eccentric overload, rescued some of the reduction in mitochondrial function seen with conventional resistance training.